Gerenciamento Dinâmico de Modelos de Contexto: Estudo de Caso Baseado em CEP - SOARES, Rodrigo Hernandez (2012)
Context models that describe dynamic context-aware scenarios usually need to be frequently updated. Some examples of situations that motivate these updates are the appearance of new services and context providers, the mobility of the entities described in these models, among others. Generally, updates on models imply redevelopment of the architectural components of context-aware systems based on these models. However, as these updates in dynamic scenarios tend to be more frequent, it is desirable that they occur at runtime. This dissertation presents an infrastructure for dynamic management of context models based on the fundamentals of complex event processing, or CEP. This infrastructure allows the fundamental abstractions from which a model is built to be updated at runtime. As these updates can impact systems based on the updated models, this dissertation identifies and analyzes these impacts, which are reproduced in a case study that aims to evaluate the proposed infrastructure by demonstrating how it deals with the impacts mentioned.